ENHANCING OPERATIONAL PERFORMANCE WITH TOTAL QUALITY MANAGEMENT IN THE HOUSING AND SETTLEMENT DEPARTMENT OF KUTAI KARTANEGARA - Restu Irawan; Zainal Abidin; Ike Purnamasari (RADJA PUBLIKA, 2026)
This study aims to examine the application of Total Quality Management (TQM) principles in the formulation of the Annual Work Plan (RKT) at the Housing and Settlement Department of Kutai Kartanegara Regency and to identify factors hindering its implementation. This research employed a qualitative approach involving eight informants. The findings show that the implementation of TQM principles, including customer focus, continuous improvement, and teamwork, contributed to improving planning quality and program execution. Customer focus ensured that the RKT was prepared based on community needs, while continuous improvement encouraged regular evaluation and enhancement of planning processes. Teamwork among departments strengthened coordination and supported more effective work plan preparation. However, several obstacles were identified, including inaccurate data, limited resources, and weak interdepartmental coordination, which reduced planning effectiveness and hindered program implementation. Therefore, improving data accuracy, strengthening coordination, and providing adequate resources are necessary to support more effective and efficient implementation of work programs.